Investigating Zinc Tolerance in Saline and Drought Tolerant Ruta graveolens Tissue Cultures - Lateef, Zainab M; Ibrahim, Kadhim M; Jabir, Abdulwahid S (Al-Nahrain Journal of Science, 2018)
Tolerance of Rutagraveolens to Zn was investigated in vitro. Heavy metal stress was induced by subculturing salt and drought tolerant callus pieces weighting 100 mg on Murashige and Skoog (MS) medium supplemented with 1 mg/l 2,4-dichlorophenoxy acetic acid (2,4-D) and 0.5 mg/l kinetin (kin). Zn was added at concentrations 0.1, 0.5, 1.0, 2.0 or 3.0 ppm. Results showed that callus relative fresh weight (RFW) decreased with increasing metal concentrations. Tolerance index (TI) was assessed at different metal concentrations and stress durations. Results also indicated that callus cultures were more tolerant to heavy metals at the concentration 1 ppm. Spectrophotometric estimation of metal concentrations inside plant tissue samples showed that callus cultures stand for moderately high concentrations of Zn reached 7100 µg/g dry weight. Heavy metal tolerant calli were selected and shoots were regenerated on ½ MS medium supplemented with 2.5 mg/l Benzyl adenine (BA).